Composite aramid insulation paper and preparation method thereof

By uniformly dispersing the aminolated carbon nanotubes in composite aramid insulating paper and using electrospinning technology, the problems of poor interface bonding and poor dispersion are solved, and the strength, toughness and thermal conductivity of the composite material are significantly improved, and the reliability of the power equipment is improved.

CN119800761AActive Publication Date: 2025-04-11ELECTRIC POWER RES INST CHINA SOUTHERN POWER GRID CO LTD +1

Patent Information

Application Number
CN202510216781.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-04-11
Estimated Expiration
2045-02-26

AI Technical Summary

Technical Problem

The existing methods cannot fundamentally solve the problems of poor interface bonding and poor dispersion when introducing a single aramid fiber into the composite material, resulting in a reduced reliability of power equipment operation.

Method used

By dispersing the aminocarbon nanotubes evenly in the matrix of aramid fibers and electrospinning is performed using polyvinylpyrrolidone as a medium to form composite aramid insulating paper. The method includes plasma treatment of carbon nanotubes, dissolution treatment of aramid fibers, electrospinning of aminolated carbon nanotubes and polyvinylpyrrolidone, blending and high-speed shearing of composite fibers and aramid fibers, and vacuum filtration to obtain composite aramid insulating paper.

Benefits of technology

It significantly improves the overall strength and toughness of composite aramid insulating paper, forms an efficient heat conduction channel, quickly conducts heat, reduces the operating temperature of power equipment, and improves the working efficiency and reliability of equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800761A_ABST
    Figure CN119800761A_ABST
Patent Text Reader

Abstract

The invention discloses composite aramid insulation paper and a preparation method thereof, and relates to the technical field of insulation materials, the composite aramid insulation paper comprises polyvinylpyrrolidone, aramid fibers and aminated carbon nanotubes, the aminated carbon nanotubes are uniformly dispersed in an aramid fiber matrix, and the mass ratio of the aminated carbon nanotubes to the composite aramid insulation paper is 5%-10%. The mass ratio of the aramid fibers to the aminated carbon nanotubes to the polyvinylpyrrolidone to the aramid fibers is (60-70): (5-10): (5-15): (15-20). The problem that existing methods are mostly limited to introduction of single aramid fibers into the composite material is solved. Through simple physical mixing or surface modification, although the performance of the composite material can be improved to a certain extent, the problems of poor interface bonding force, poor dispersity and the like cannot be fundamentally solved, and the technical problem that the operation reliability of power equipment is reduced is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of insulating materials, and in particular to a composite aramid insulating paper and a preparation method thereof. Background Art

[0002] With the rapid development of the electric power industry and high-tech equipment, the performance requirements for power insulation materials are getting higher and higher, especially in high voltage, high temperature and high load environments. Traditional insulation materials have gradually been unable to meet these demanding requirements. Aramid fiber has become an important component of power equipment, aerospace, military protection and high-performance composite materials due to its excellent mechanical properties, high temperature resistance and good electrical insulation. Aramid fiber not only has high tensile strength and excellent thermal stability, but also has good electrical insulation properties. It is widely used in the fields of insulation paper and reinforced fiber materials for power equipment. However, traditional aramid insulation paper still has some shortcomings, especially in terms of impact resistance, thermal conductivity, toughness and other aspects. There is a lot of room for improvement. Therefore, it is urgent to modify and compound aramid fibers to achieve higher performance.

[0003] Currently, most existing methods are limited to introducing a single aramid fiber into a composite material. Although simple physical mixing or surface modification can improve the performance of the composite material to a certain extent, it cannot fundamentally solve the problems of poor interface bonding and poor dispersion, which reduces the reliability of power equipment operation. Summary of the invention

[0004] The present invention provides a composite aramid insulation paper and a preparation method thereof, which solves the technical problem that most existing methods are limited to introducing a single aramid fiber into a composite material. Although the performance of the composite material can be improved to a certain extent through simple physical mixing or surface modification, it cannot fundamentally solve the problems of poor interface bonding and poor dispersion, thereby reducing the reliability of power equipment operation.

[0005] A first aspect of the present invention provides a composite aramid insulation paper, the composite aramid insulation paper comprising polyvinyl pyrrolidone, aramid fibers and amino carbon nanotubes;

[0006] The amino carbon nanotubes are uniformly dispersed in the matrix of the aramid fiber.

[0007] Optionally, the mass ratio of the amino-treated carbon nanotubes to the composite aramid insulation paper is 5%-10%.

[0008] Optionally, the mass ratio of the aramid fiber, the amino carbon nanotube, the polyvinyl pyrrolidone and the aramid fiber is 60-70:5-10:5-15:15-20.

[0009] A second aspect of the present invention provides a method for preparing the composite aramid insulation paper, characterized by comprising:

[0010] The carbon nanotubes are subjected to plasma treatment to obtain amino-treated carbon nanotubes;

[0011] Based on the previously obtained dimethyl sulfoxide solution, the aramid fiber is dissolved to obtain an aramid fiber gel;

[0012] Based on the pre-obtained polyvinyl pyrrolidone, the amino-modified carbon nanotubes are subjected to electrospinning to obtain target composite fibers;

[0013] The target composite fiber and the aramid fiber gel are sequentially blended and high-speed sheared to obtain the target composite fiber gel;

[0014] The target composite fiber gel is subjected to vacuum filtration operation to obtain composite aramid insulation paper.

[0015] Optionally, the step of using carbon nanotubes for plasma treatment to obtain amination carbon nanotubes comprises:

[0016] Using a preset mixed cleaning solution to remove impurities from the carbon nanotubes to obtain target carbon nanotubes, wherein the mixed cleaning solution is a mixed solution of concentrated nitric acid and sulfuric acid;

[0017] Based on a preset reaction temperature range, using a preset ammonia water to perform a bonding reaction on the target carbon nanotubes to obtain initial amination carbon nanotubes;

[0018] The initial aminated carbon nanotubes are subjected to ultrasonic dispersion treatment to obtain aminated carbon nanotubes.

[0019] Optionally, the step of dissolving the aramid fiber based on the pre-obtained dimethyl sulfoxide solution to obtain the aramid fiber gel comprises:

[0020] The aramid fiber is subjected to a dissolving pretreatment to obtain a target aramid fiber;

[0021] adding the target aramid fiber to a pre-obtained dimethyl sulfoxide solution to generate an aramid fiber mixed solution;

[0022] The aramid fiber mixed liquid is subjected to ultrasonic dispersion and stirring operations to obtain an aramid fiber gel.

[0023] Optionally, the step of performing electrospinning operation on the amino-modified carbon nanotubes based on the pre-acquired polyvinyl pyrrolidone to obtain the target composite fiber comprises:

[0024] Adding the amino-modified carbon nanotubes into pre-obtained polyvinyl pyrrolidone and performing ultrasonic dispersion operation to obtain a target spinning solution, wherein the concentration of the target spinning solution is 10%-15%;

[0025] Based on a preset spinning voltage interval, the target spinning solution is electrospun to obtain a target composite fiber.

[0026] Optionally, the aramid fiber includes Kevlar fiber, Nomex fiber, Twaron fiber or Technora fiber.

[0027] Optionally, the reaction temperature range is 60-80 degrees.

[0028] Optionally, the spinning voltage range is 10-20 kV.

[0029] It can be seen from the above technical solutions that the present invention has the following advantages:

[0030] 1. The composite aramid insulation paper provided by the present invention is composited with polyvinyl pyrrolidone, aramid fiber and amino carbon nanotubes, which significantly improves the overall strength of the composite aramid insulation paper. At the same time, the amino carbon nanotubes are evenly dispersed in the matrix of the aramid fiber, so that the composite aramid insulation paper can effectively disperse stress when subjected to force, avoiding local stress concentration, thereby greatly improving the toughness of the composite aramid insulation paper.

[0031] 2. The present invention evenly disperses the amino carbon nanotubes in the aramid fiber matrix, so that an efficient heat conduction channel is formed in the composite aramid insulation paper, which can quickly conduct heat away, effectively reduce the operating temperature of power equipment, improve the working efficiency and reliability of power equipment, and reduce the risk of failure and damage caused by overheating.

[0032] 3. The present invention composites amino carbon nanotubes with aramid fibers through electrostatic spinning to form composite aramid insulation paper, which maintains the original electrical insulation performance and high temperature resistance of the aramid fibers. At the same time, the dispersion of the carbon nanotubes is improved through amino modification, so that they can form a strong interface bond with the aramid fibers, thereby improving the thermal conductivity and toughness of the composite aramid insulation paper. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0034] Figure 1A schematic diagram showing a comparison of mechanical and thermal conductivity properties between the composite aramid insulation paper provided by an embodiment of the present invention and traditional aramid insulation paper;

[0035] Figure 2 A schematic diagram of the preparation process of the aramid fiber gel provided in an embodiment of the present invention;

[0036] Figure 3 The embodiment of the present invention provides Schematic diagram of the vacuum filtration process of composite fiber / ANF aramid fiber;

[0037] Figure 4 It is a schematic diagram comparing the experimental results of Examples 1 to 7 of the present invention and Comparative Examples 1 to 3. DETAILED DESCRIPTION

[0038] The embodiment of the present invention provides a composite aramid insulation paper and a preparation method thereof, which is used to solve the technical problem that most existing methods are limited to introducing a single aramid fiber into a composite material. Although the performance of the composite material can be improved to a certain extent through simple physical mixing or surface modification, it cannot fundamentally solve the problems of poor interface bonding and poor dispersion, thereby reducing the reliability of power equipment operation.

[0039] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] See also Figure 1-Figure 3 As shown, the present invention provides a composite aramid insulation paper, which includes polyvinyl pyrrolidone, aramid fibers and amino carbon nanotubes, wherein the amino carbon nanotubes are uniformly dispersed in a matrix of the aramid fibers.

[0041] In the embodiment of the present invention, the composite aramid insulation paper presents a nanocomposite structure from a microscopic level, and the carbon nanotubes treated with amino are evenly dispersed in the aramid fiber matrix, and the two are closely combined. The carbon nanotubes are like tiny "reinforced skeletons", which strengthen the stability and strength of the overall structure at the nanoscale. At the same time, it also has a fiber network structure. Through electrospinning, blending, high-speed shearing, and vacuum filtration and other process steps, the composite fibers and aramid fibers are intertwined and entangled to form an intricate and orderly fiber network. This network structure is not only conducive to the uniform transfer and dispersion of stress inside the material, greatly improving the toughness and strength of the material, but also provides a multi-dimensional path for the conduction of heat, which helps to achieve high thermal conductivity, so that the composite aramid insulation paper shows a high degree of synergy and optimization in structure.

[0042] The raw materials and reagents involved in the embodiments of the present invention are all commercially available.

[0043] In order to further illustrate the present invention, a composite aramid insulation paper and a preparation method thereof provided by the present invention are described in detail below in conjunction with embodiments.

[0044] Embodiment 1

[0045] Embodiment 1 of the present invention is a preparation of a composite aramid insulation paper, wherein the composite aramid insulation paper is made of carbon nanotubes (CNT) subjected to an amino treatment ( ) and then composited with aramid fiber (ANF). A method for preparing composite aramid insulation paper includes:

[0046] Step 101: Starting from carbon nanotubes (CNT), amino functional groups are grafted onto the surface of the CNTs through plasma treatment to obtain amino carbon nanotubes ( );

[0047] Furthermore, step 101 includes the following sub-steps:

[0048] S11. Reacting multi-walled carbon nanotubes (MWCNTs) with a mixed solution of concentrated nitric acid and sulfuric acid to remove surface impurities and increase surface activity.

[0049] It should be noted that during the reaction with the mixed solution of concentrated nitric acid and sulfuric acid, the treatment was carried out at a power of 100 W, a treatment time of 30 minutes, a gas flow rate of 20 sccm, and a pressure controlled at 0.2 mbar.

[0050] S12, the washed carbon nanotubes and ammonia water (25% ) are mixed and reacted at 60-80°C to form amino carbon nanotubes.

[0051] It should be noted that, the reaction was carried out at 60-80°C for 2 hours, and the amino group ( ) functional groups will react with the surface of carbon nanotubes to form amino-modified carbon nanotubes.

[0052] S13, the reaction Ultrasonic dispersion is performed to obtain the treated .

[0053] It should be noted that after the reaction Ultrasonic dispersion is required to ensure uniform dispersion and avoid agglomeration.

[0054] It is worth mentioning that carbon nanotubes ( ) is compounded with aramid fiber (ANF) after amino treatment to form a composite structure with high toughness and high strength. Aminated carbon nanotubes not only improve the mechanical properties of the fiber, making it have higher tensile strength and wear resistance, but also, due to its nano-scale size, can effectively improve the overall rigidity of the composite material and enhance its tear and compression resistance.

[0055] Step 102, treating aramid fiber (ANF) in a dimethyl sulfoxide (DMSO) system to obtain ANF gel;

[0056] It should be noted that step 102 specifically includes: cutting aramid fiber (such as Kevlar®) into small segments of 2 cm in length, and placing the aramid fiber in DMSO at a ratio of 20 wt% aramid fiber to 80 wt% DMSO, using heating and stirring to help the aramid fiber dissolve and form a gel state (wherein the reaction temperature is set to 80°C and the reaction time is 2 hours), ensuring that the aramid fiber is completely dissolved and evenly dispersed. Finally, an aramid fiber gel (ANF gel) is obtained.

[0057] It should be noted that the amount of aramid fiber (ANF) is usually 60%-70% of the total weight of the composite material, which is used to provide the main mechanical strength and electrical insulation of the material. The size of aramid fiber is usually small segments or short fibers with a length of 1-2 mm, which can be fully dissolved in dimethyl sulfoxide (DMSO). The solubility ratio of aramid fiber in DMSO is about 10-20% concentration (that is, 10-20 grams of aramid fiber is dissolved in 100 ml of DMSO). Through ultrasonic and stirring processes, the aramid fiber is completely dissolved in dimethyl sulfoxide (DMSO) to form a uniform aramid gel.

[0058] It is worth mentioning that aramid fiber itself has excellent high temperature resistance and can maintain its physical properties in high temperature environment, while the addition of CNT further improves the thermal conductivity of the composite material, ensuring that the material can effectively dissipate heat in an environment with high heat load and prevent damage caused by heat accumulation.

[0059] Step 103: amination of carbon nanotubes ( ) was ultrasonically dispersed in polyvinylpyrrolidone (PVP) to obtain Spinning solution;

[0060] It should be noted that the concentration of polyvinyl pyrrolidone (PVP) is 0.5 wt %, and the concentration of amino-modified carbon nanotubes is 0.5 wt %.

[0061] It should be noted that during the ultrasonic dispersion process, the ultrasonic frequency was set to 40 kHz and the dispersion time was 1 hour.

[0062] Step 104: Obtaining by electrospinning Composite fibers;

[0063] It should be noted that during the electrospinning process, the required The concentration of the solution is usually 10%-15%. The injection volume of the solution was approximately 5–10 mL, while the electrospinning voltage was set to 15 kV, the distance between the nozzle and the collecting plate was typically maintained at 10 cm and the feed rate was 0.5 mL / h.

[0064] It should be noted that during the electrospinning process, the feed rate was 0.5 mL / h.

[0065] It should be noted that during the electrospinning process, the solution is stretched into nano-scale fibers by a strong electric field and collected on aluminum foil. The diameter of the composite fiber after spinning is controlled between 100-500 nm, and the surface is smooth, evenly distributed and has no agglomeration, ensuring that it can effectively perform in the subsequent steps.

[0066] Step 105: The composite fiber was blended with ANF gel and subjected to high-speed shearing to obtain Composite fiber / ANF aramid fiber;

[0067] It should be noted that in step 105, The composite fiber is mixed with aramid fiber gel (ANF gel) in a ratio of 1:3 by mass of the composite fiber to the gel.

[0068] It should be noted that when high-speed shearing is performed, the shear rate is set to 2000 rpm and the shearing time is 30 minutes to ensure that the composite fiber and the gel are fully and evenly mixed.

[0069] It is worth mentioning that through step 105, the interaction between the fiber and the gel is enhanced to form a uniform / ANF composite fiber / ANF aramid fiber.

[0070] Step 106: / ANF composite fiber / ANF aramid fiber is vacuum filtered to obtain composite aramid insulation paper.

[0071] It should be noted that during the filtration process, the vacuum pressure was controlled at 0.1 MPa and lasted for 2 hours to ensure that the fibers were evenly distributed on the filter medium to form a stable fiber network.

[0072] It should be noted that after the filtration, the obtained composite material was dried at 60°C for 12 hours to ensure complete removal of the solvent and obtain a strong composite material.

[0073] It is worth mentioning that the high electrical insulation of aramid fiber combined with the excellent conductivity of carbon nanotubes makes the composite aramid insulation paper have good insulation properties and can be flexibly adjusted in certain applications that require conductivity to achieve higher adaptability. At the same time, the chemical corrosion resistance of the composite aramid insulation paper has also been significantly improved, and it can withstand the erosion of various chemical media and adapt to long-term use in complex environments.

[0074] It is worth mentioning that the composite aramid insulation paper has low hygroscopicity and is not easily affected by moisture, which further improves the stability of the composite aramid insulation paper in a humid environment.

[0075] It should be noted that, through the preparation steps 101-106, it can be seen that the aramid fibers and the amino-modified carbon nanotubes ( ) has a mass ratio of 10:1.

[0076] Embodiment 2

[0077] Embodiment 2 of the present invention is a method for preparing a composite aramid insulation paper, wherein the composite aramid insulation paper comprises polyvinyl pyrrolidone, aramid fibers and amino carbon nanotubes. The method for preparing the composite aramid insulation paper comprises:

[0078] Step 201, amination of carbon nanotubes ( Preparation of MWCNTs: First, the selected multi-walled carbon nanotubes (MWCNTs) were treated with plasma to remove surface impurities and increase their surface activity. The specific operation was to treat them in an oxygen plasma environment with a power of 100 W, a treatment time of 30 minutes, a gas flow rate of 20 sccm, and a pressure controlled at 0.2 mbar. After the treatment, the carbon nanotubes were immersed in concentrated ammonia (25%) ), and the reaction time is 2 hours. This step successfully grafts amino functional groups onto the surface of carbon nanotubes to obtain amino groups.

[0079] Step 202: See Figure 2As shown in the figure, the preparation of aramid fiber (ANF) gel: Aramid fiber (such as Kevlar®) is cut into small pieces of 2 cm long and treated in dimethyl sulfoxide (DMSO) solution. Aramid fiber is placed in DMSO at a ratio of 20 wt% aramid fiber to 80 wt% DMSO, and heating and stirring are used to help the aramid fiber dissolve to form a gel state. The reaction temperature is set to 80°C and the reaction time is 2 hours to ensure that the aramid fiber is completely dissolved and evenly dispersed. Finally, aramid fiber gel (ANF gel) is obtained. The key to this step is to ensure the uniformity and stability of the gel by reasonably controlling the dissolution temperature and time.

[0080] Step 203: Preparation of spinning solution: First, the amino carbon nanotubes ( Ultrasonic dispersion was performed in polyvinylpyrrolidone (PVP) solution. We used 0.5 wt% PVP solution and 0.5 wt% CNT-NH2 to ensure Good dispersibility. In the ultrasonic cleaning machine, the ultrasonic frequency was set to 40 kHz and the dispersion time was 1 hour to ensure Evenly distributed in the PVP solution. After dispersion, a uniform Spinning solution, which lays the foundation for the subsequent electrospinning step.

[0081] Step 204: Electrospinning of composite fibers: The prepared The spinning solution was spun by electrospinning. The voltage during electrospinning was set to 15 kV, the spinning distance was set to 10 cm, and the feed rate was 0.5 mL / h. The temperature of the collecting plate was maintained at 25°C to ensure that the fibers were formed under good environmental conditions. During the electrospinning process, the solution was stretched by a strong electric field to form nano-scale fibers, which were collected on aluminum foil. The diameter of the composite fiber after spinning was controlled between 100-500 nm, and the surface was smooth, evenly distributed without agglomeration, ensuring that it can effectively perform its performance in subsequent steps.

[0082] Step 205 / ANF composite fiber / ANF aramid fiber preparation: The composite fiber was mixed with aramid fiber gel (ANF gel) at a mass ratio of 1:3. The mixture was placed in a high-speed shearing machine with a shear rate of 2000 rpm and a shear time of 30 minutes to ensure that the composite fiber and gel were fully and evenly mixed. Through this process, the interaction between the fiber and gel was enhanced to form a uniform Composite fiber / ANF aramid fiber, this gel will be used as the vacuum filtration material in the next step.

[0083] Step 206, see Figure 3 As shown, the preparation of composite aramid insulation paper: / ANF composite fiber / ANF aramid fiber was vacuum filtered to remove excess solvent. During the filtration process, the vacuum pressure was controlled at 0.1 MPa and lasted for 2 hours to ensure that the fibers were evenly distributed on the filter medium and formed a stable fiber network. After the filtration was completed, the obtained composite material was dried at 60°C for 12 hours to ensure complete removal of the solvent and obtain a strong composite material.

[0084] It should be noted that aramid fibers and amino carbon nanotubes ( ) has a mass ratio of 7:3.

[0085] It is worth mentioning that the dried composite aramid insulation paper has excellent high toughness, high strength and high thermal conductivity, and is suitable for high-performance thermal insulation and insulation applications.

[0086] Embodiment 3

[0087] Compared with Example 1, this embodiment has aramid fibers and amino-modified carbon nanotubes ( ) was set to a mass ratio of 6:4, and the rest of the steps remained unchanged.

[0088] Embodiment 4

[0089] Compared with Example 1, this embodiment has aramid fibers and amino-modified carbon nanotubes ( ) is 5:5, and the other steps remain unchanged.

[0090] Embodiment 5

[0091] Compared with the first embodiment, the mixing ratio of the composite fiber to the aramid fiber gel in this embodiment is 1:2, and the other steps remain unchanged.

[0092] Comparative Example 1

[0093] Compared with Example 1, this comparative example mixes aramid fiber and synthetic carbon nanotubes by high-speed shearing to obtain aramid carbon nanotube composite slurry, obtains aramid carbon nanotube paper by electrostatic spinning, and obtains traditional aramid carbon nanotube insulation paper by high-temperature hot pressing. ) is surface modified and does not go through the composite fiber / aramid fiber preparation step.

[0094] Comparative Example 2

[0095] Compared with Example 1, the composite fiber of this comparative example only uses aramid fiber without adding amino carbon nanotubes ( ), the rest of the steps remain unchanged.

[0096] Comparative Example 3

[0097] Compared with Example 1, the composite fiber in this comparative example only uses aramid fiber and polyvinyl pyrrolidone (PVP) solution, and no amino carbon nanotubes ( ) is compounded with aramid fiber gel, and the other steps remain unchanged.

[0098] See also Figure 4 As shown, by comparing the thermal conductivity of the composite aramid insulation paper in Examples 1 to 5 and Comparative Examples 1 to 3, it can be seen that the thermal conductivity of the composite aramid insulation paper in Examples 1 to 5 is significantly higher than that of the composite aramid insulation paper in Comparative Examples 1 to 3 (wherein the thermal conductivity of the composite aramid insulation paper in Example 1 is The thermal conductivity of the composite aramid insulation paper in comparative example 2 is ). It can be seen that by introducing amino carbon nanotubes ( ), which makes the composite aramid insulation paper have better thermal conductivity.

[0099] See also Figure 4 As shown, by comparing the tensile strength of the composite aramid insulation paper in Examples 1 to 5 and Comparative Examples 1 to 3, it can be seen that the tensile strength of the composite aramid insulation paper in Example 1 is 315 MPa, and the tensile strength of the composite aramid insulation paper in the comparative example is 149.5 MPa. It can be seen that the preparation method of the present invention can significantly improve the mechanical strength of the composite material.

[0100] See also Figure 4 As shown, by comparing the Young's modulus of the composite aramid insulation paper in Examples 1 to 3 and Comparative Examples 1 to 3, it can be seen that the Young's modulus of the composite aramid insulation paper in Example 1 is 10.14 GPa, and the Young's modulus of the composite aramid insulation paper in Comparative Example 2 is 4.83 GPa. It can be seen that the composite aramid insulation paper in the present invention maintains a high rigidity while improving thermal conductivity and strength, and has good mechanical properties.

[0101] See also Figure 4 As shown, the composite aramid insulation paper in Examples 1 to 7 shows significant superiority in thermal conductivity, tensile strength and Young's modulus. Compared with Comparative Example 2, the mechanical strength, thermal conductivity and rigidity of the composite aramid insulation paper are significantly improved. Compared with the traditional method for preparing composite aramid insulation paper, the present invention introduces amino carbon nanotubes ( ) and adopts composite fiber / aramid fiber preparation technology to effectively improve the comprehensive performance of composite aramid insulation paper.

[0102] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A composite aramid insulation paper, characterized in that: The composite aramid insulation paper comprises polyvinyl pyrrolidone, aramid fibers and amino carbon nanotubes; The amino carbon nanotubes are uniformly dispersed in the matrix of the aramid fiber.

2. The composite aramid insulation paper according to claim 1, characterized in that: The mass ratio of the amino carbon nanotubes to the composite aramid insulation paper is 5%-10%.

3. The composite aramid insulation paper according to claim 1, characterized in that: The mass ratio of the aramid fiber, the amino carbon nanotube, the polyvinyl pyrrolidone and the aramid fiber is 60-70: 5-10: 5-15: 15-20.

4. A method for preparing the composite aramid insulation paper according to any one of claims 1 to 3, characterized in that: include: The carbon nanotubes are subjected to plasma treatment to obtain amino-treated carbon nanotubes; Based on the previously obtained dimethyl sulfoxide solution, the aramid fiber is dissolved to obtain an aramid fiber gel; Based on the pre-obtained polyvinyl pyrrolidone, the amino-modified carbon nanotubes are subjected to electrospinning to obtain target composite fibers; The target composite fiber and the aramid fiber gel are sequentially blended and high-speed sheared to obtain the target composite fiber gel; The target composite fiber gel is subjected to vacuum filtration operation to obtain composite aramid insulation paper.

5. The method for preparing composite aramid insulation paper according to claim 4, characterized in that: The step of using carbon nanotubes for plasma treatment to obtain amino carbon nanotubes comprises: Using a preset mixed cleaning solution to remove impurities from the carbon nanotubes to obtain target carbon nanotubes, wherein the mixed cleaning solution is a mixed solution of concentrated nitric acid and sulfuric acid; Based on a preset reaction temperature range, using a preset ammonia water to perform a bonding reaction on the target carbon nanotubes to obtain initial amination carbon nanotubes; The initial aminated carbon nanotubes are subjected to ultrasonic dispersion treatment to obtain aminated carbon nanotubes.

6. The method for preparing composite aramid insulation paper according to claim 4, characterized in that: The step of dissolving the aramid fiber based on the pre-obtained dimethyl sulfoxide solution to obtain the aramid fiber gel comprises: The aramid fiber is subjected to a dissolving pretreatment to obtain a target aramid fiber; adding the target aramid fiber to a pre-obtained dimethyl sulfoxide solution to generate an aramid fiber mixed solution; The aramid fiber mixed liquid is subjected to ultrasonic dispersion and stirring operations to obtain an aramid fiber gel.

7. The method for preparing composite aramid insulation paper according to claim 4, characterized in that: The step of electrospinning the amino-modified carbon nanotubes based on the pre-obtained polyvinyl pyrrolidone to obtain the target composite fiber comprises: Adding the amino-modified carbon nanotubes into pre-obtained polyvinyl pyrrolidone and performing ultrasonic dispersion operation to obtain a target spinning solution, wherein the concentration of the target spinning solution is 10%-15%; Based on a preset spinning voltage interval, the target spinning solution is electrospun to obtain a target composite fiber.

8. The method for preparing composite aramid insulation paper according to claim 4, characterized in that: The aramid fiber includes Kevlar fiber, Nomex fiber, Twaron fiber or Technora fiber.

9. The method for preparing composite aramid insulation paper according to claim 5, characterized in that: The reaction temperature range is 60-80°C.

10. The method for preparing composite aramid insulation paper according to claim 7, characterized in that: The spinning voltage range is 10-20 kV.

Citation Information

Patent Citations

  • Method for modifying aramid fiber by using carbon nano tubes

    CN101831800A

  • Carbon nanotube modified aramid III fiber and preparation method thereof

    CN117089941A

  • Aramid / carbon nanotube composites fiber and method for preparing the same

    KR1020150079151A

  • Spinning dope for aramid and carbon-nanotube composite fiber and method of manufacturing aramid and carbon-nanotube composite fiber using same

    US20230114595A1

Cited By

  • Aramid fiber composite insulation paper and preparation method thereof

    CN121228561A